Instalaciones y equipamiento vitivinícola en el reino de Chile. Vasijas, pipas, lagares (siglo XVIII) - Lacoste, Pablo (Revista de Historia Social y de las Mentalidades, 2025)
This article studies the equipment and installation s of wine industry in Chile’s Kingdom during XVIII century. The topic is relevant because at that time, Chile was the most important wine industry center in America. The pape r explores the different kinds of wine vessel and containers. Chilean wine industry used p otter’s clay vessel between XVI and XIX centuries. This was the golden age of vessel furnace. But since 1750 it began to decline because the introduction of wood vessel (ba rrels). This equipment made possible the development of one of the most important indust ries during Spanish period in South America.